2018
DOI: 10.1111/jgh.14403
|View full text |Cite
|
Sign up to set email alerts
|

Clinical, endoscopic, and histological differentiation between celiac disease and tropical sprue: A systematic review

Abstract: Both patients with CD and TS have overlapping clinical, endoscopic, and histological characteristics, and there is no single diagnostic feature for differentiating CD from TS except for celiac specific serological tests.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 41 publications
1
5
0
1
Order By: Relevance
“…5 In our series we found 59 (63.4%) out of 93 patients to be vitamin B 12 deficient. 18 Considering the hematological parameters, mean hemoglobin and mean corpuscular volume (MCV) of the patients were 6.68 g/dL and 103.9 fL, respectively. MCV was less than 90 fL in five patients (5%).…”
Section: Resultsmentioning
confidence: 92%
“…5 In our series we found 59 (63.4%) out of 93 patients to be vitamin B 12 deficient. 18 Considering the hematological parameters, mean hemoglobin and mean corpuscular volume (MCV) of the patients were 6.68 g/dL and 103.9 fL, respectively. MCV was less than 90 fL in five patients (5%).…”
Section: Resultsmentioning
confidence: 92%
“…This could be because subtle endoscopic changes were not documented since duodenal biopsies were routinely done in all the patients with megaloblastic anemia. However, Sharma et al 18 in their systematic review had found normal duodenal folds to be more common in TS.…”
Section: Discussionmentioning
confidence: 95%
“…Autoimmune and immune-mediated diseases Autoimmune enteropathy [16] Crohn's disease [17] Collagenous sprue [18] Common variable immune deficiency (CVID) [19] Infectious or probably infectious diseases Giardia lamblia infection [20] Helicobacter pylori infection [17] Post-viral enteropathy [21] Tuberculosis [22] Small intestinal bacterial overgrowth [23] HIV-enteropathy [24] Whipple disease [25] Tropical sprue [26] Iatrogenic causes Medication (angiotensin II receptor blockers [27], mefenamic acid [28], azathioprine [29], methotrexate [30], mycophenolate mofetil [31]) Chemotherapy [32] Radiotherapy [33] Graft versus host disease [34] Inflammatory disease Peptic duodenitis [35] Eosinophilic gastroenteritis [36] Neoplastic Small intestinal lymphoma [37] Other Amyloidosis [38] Malnutrition [39] Food allergy (cow's milk, soy) [20] According to the few studies available on the subject, the frequency of occurrence of SNVA varies considerably, particularly between adult and child populations. CD is diagnosed in 28-45% of adults with SNVA [5,13,40]; among the remainder, the most common causes of non-CD SNVA are believed to be inter alia medication-related enteropathy and infectious causes, including giardiasis and small intestinal bacterial overgrowth, peptic duodenitis, and collagenous sprue [5,13,40,41].…”
Section: Aetiology Of Non-coeliac Seronegative Villous Atrophymentioning
confidence: 99%